Low exposure to direct oral anticoagulants is associated with ischemic stroke and its severity - Rizos, Timolaos; Meid, Andreas; Huppertz, Andrea; Dumschat, Chris; Purrucker, Jan; Foerster, Kathrin; Burhenne, Jürgen; Czock, David; Jenetzky, Ekkehart; Ringleb, Peter A.; Haefeli, Walter E. (Journal of stroke, 2022)
Background and purpose: In acute stroke patients, plasma concentrations of direct oral anticoagulants (DOAC) at hospital admission only poorly mirror DOAC exposure or the coagulation status at the time of the event. Here, we evaluated whether DOAC exposure and DOAC plasma concentration at the time of transient ischemic attacks (TIA) and ischemic strokes correlate with their likelihood of occurrence. Methods: Prospectively, consecutive DOAC patients with acute ischemic stroke or TIA were included. Admission DOAC plasma concentrations were measured by ultraperformance liquid chromatography-tandem mass spectrometry. Individual DOAC exposure (area under the curve) and DOAC concentrations at event onset were derived from population pharmacokinetic analyses. Results: DOAC exposure was successfully modeled in 211 patients (ischemic stroke 74.4%, TIA 25.6%). Compared to published values, 63.0% had relatively lower DOAC exposure and they more often received lower DOAC doses than recommended (odds ratio [OR], 2.125; 95% confidence interval [CI], 1.039 to 4.560; P=0.044). These patients more likely suffered ischemic strokes than TIA (OR, 2.411; 95% CI, 1.254 to 4.638; P=0.008) and their strokes were more severe (slope, 3.161; 95% CI, 0.741 to 5.58; P=0.011). Low relative DOAC concentrations at event onset were likewise associated with ischemic strokes (OR, 4.123; 95% CI, 1.834 to 9.268; P=0.001), but not to stroke severity (P=0.272). DOAC exposure had a higher explanatory value for stroke severity than concentrations at event. Conclusions: Low DOAC exposure is strongly associated to ischemic stroke and its severity. By monitoring DOAC plasma concentrations, patients prone to ischemic stroke might be identified.
Mit ergänzenden Materialien für diesen Artikel
Gesehen am 21.06.2022